Hubungan Frekuensi Pemberian ERYTHROPOIETIN STIMULATING AGENT (ESA) Dengan Peningkatan Hemoglobin Pasien Hemodialisa Di RSUD Ciawi - Nurafni, Silvi; Desminingrum, Tri; Samsiah, Siti (Jurnal Farmasi & Sains Indonesia, 2023)
Anemia complicated by CKD occurs 80-90% due to deficiency of erythropoietin. Erythropoietin Stimulating Agent (ESA) therapy is the main choice at Ciawi Hospital. Chronic Kidney Failure (CKD) is the 7th 10th biggest disease in Ciawi Hospital. The aim of the study was to evaluate the success of Erythropoietin Stimulating Agent (ESA) treatment in Hemodialysis (HD) patients at Ciawi General Hospital. This research is descriptive in nature, collecting retrospective data from secondary data from medical records, laboratory data from Hb patients. Sampling was taken using the total sampling method, namely all outpatient Hemodialysis (HD) patients at the Ciawi Hospital for the period October-December 2021 who met the inclusion and exclusion criteria totaling 47 patients. The results of this study show the sociodemographic picture of patients with Chronic Kidney Failure (CKD) with anemia complications, the most age range being 46-55 years, 18 patients (38.30%), the most sex being male, 25 patients (53.19%). The description of the duration of Hemodialysis (HD) therapy is that the most ? 12 months 27 patients (57.45%). The description of the highest frequency of ESA administration was at a frequency of 2 times a month with the Hb category increasing by 21 patients (63.6%) and the Hb category decreasing by 12 patients (36.4%). There is no relationship between the frequency of Erythropoietin Stimulating Agent (ESA) therapy with an increase in hemoglobin values in patients with chronic kidney failure undergoing hemodialysis and suffering from anemia as indicated by a significance value (P-value) of 0.659 > 0.05.